APLIKASI LIMBAH CAIR KELAPA SAWIT DENGAN INTERVAL PEMBERIAN TERHADAP PERTUMBUHAN DAN PRODUKSI BERBAGAI VARIETAS JAGUNG MANIS (Zea mays saccharata Sturt) - Belia, Velisia Okta; Prayoga, Gigih Ibnu; Pratama, Deni (Universitas Lampung, 2025)
Palm oil plantations in recent years have grown rapidly in almost all parts of Indonesia. The existence of palm oil mills has positive and negative impacts. The negative impact for the community is liquid waste, But can utilized for agricultural purpose such as by using liquid waste fertilizer from palm oil mills. Sweet Corn is one of the commodities favored by the people of Indonesia because it tastes good and sweet, and contains many vitamins. However, the productivity of Sweet Corn in Bangka Belitung Islands is decreasing. This study aims to produce optimal Sweet Corn growth, by using from palm oil mills. This study used a split plot Randomized Block Design (RBD) with 3 replications. The main plot is sweet corn variety (V) consist of, V1= Super sweet variety, V2= Bonanza variety, V3= Paragon variety, and the subplot is the interval of application of palm liquid waste (P) consist of, P0= Control, P1= Interval once every 10 days, P2= Interval once every 20 days, P3= Interval once every 30 days. The results of statistical analysis showed that different varieties of sweet corn gave a significant effect on harvest age, cob diameter, cob weight with clobber, cob weight without clobber and yield per plot. Giving different intervals gives a significant effect on stem diameter and cob diameter. Bonanza variety is the best variety in sweet corn growth and production. Once every 10 days is the best interval for sweet corn growth and production. The interaction of paragon variety and interval of 10 days give the best result for the parameter of age of female flowering in sweet corn. Key words: Interval pemberian, Pupuk organik, Limbah cair kelapa sawit, Jagung manis